Tingkat Kepercayaan dan Minat Terhadap Investasi Obligasi Syariah pada Mahasiswa UIN Sunan Gunung Djati Bandung di Masa Normal Baru - Anggun Rositawati Adibrata; Neneng Hartati; Vemy Suci Asih (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study discusses the relationship between Trust Level as (X₁) and Interest as (X₂) on Sharia Bond Investment (Y) in UIN Sunan Gunung Djati Bandung students as research targets. The method used in this research is a survey method by distributing questionnaires to get 100 respondents and using a quantitative approach. The purpose of this study is to determine how much influence it has on each variable for the results of the study indicate that the Trust Level has a significant positive effect on Islamic Bond Investment. Then the students' interest in a relationship to Sharia Bond Investment is 0.578. Calculated by the correlation test and determination test.